Molecular characterisation and pathogenicity of chicken astrovirus isolated from commercial broiler chickens in Malaysia - Abdullahi, Raji Abdullahi (2021)
Chicken astrovirus (CAstV) is a ubiquitous enteric RNA virus that has been associated mainly with conditions including runting stunting syndrome, kidney and visceral gout, and white chick syndrome in broiler-type of chickens across the globe. In Malaysia, the detection of the virus amongst broiler flocks has not been studied. The description of CAstV in this chapter is based on an RT-PCR assay, serology, genome characteristics and pathogenicity of the virus in specific-pathogen-free (SPF) chickens. The viruses were detected from tissue broiler chickens suffering from kidney disease and poor performance. A total of 20 tissue samples obtained from different broiler flocks between 2017 and 2018 were confirmed positive for CAstV based on polymerase gene (ORF1b) specific RT-PCR detection. A serological study based on CAstV group B enzyme-linked immunosorbent assay (ELISA) revealed a high incidence of the virus amongst broilerbreeder flocks. The tissue samples were then used to isolate CAstV using 5- day-old SPF embryonated chicken eggs (ECE). After four passages, only three isolates, IBS503/2017, IBS543/2017 and UPM1019/2018 were isolated and considered for further studies. Three pairs of overlapping primer sets were designed to amplify a nearly complete genome sequence of the three CAstV that were propagated in SPF-ECE. The amplicons were sequenced on the Illumina MiSeq platform. The generated raw sequencing data were transferred and de novo assembled in a genome assembly software for consensus generation and mapping to reference. The analysis produced a near-complete genome sequence of the three CAstV isolates IBS503/2017, IBS543/2017 and UPM1019/2018 with the genome length of 7424bp, 7379bp and 7397bp, respectively. The genomic organisation of the three isolates exhibited three open reading frames, ORF-1a, ORF-1b, and ORF-2, that encode for trypsin-like serine protease, RNA-dependent RNA polymerase (RdRp) and capsid protein, respectively. A point mutation of guanine (G) to thymine (T) was observed in the spacer sequence between ORF-1a and ORF-1b. Additionally, a third stem-loop like motif (s2m) was observed at the 3’-end of the untranslated region (UTR). Genome analysis of the isolates at the nucleotide level with other CAstV genomes showed a similarity of 77% with group B CAstV from China, 87% with group B Indian strain, 88 to 89% with group B North American strains, and 74% similarity with group A CAstV from Poland. However, analysis based on the capsid gene sequences classified the isolated viruses as group B CAstV, showing a sequence similarity at the nucleotide level (91.96 to 93.78%) and amino acid (90.51 to 93.63%) with CAstV isolates in subgroup Bi, Biii and Biv. Sequence similarity of 76.18 to 90.09% and 86.02 to 89.97% at nucleotide and amino acid levels, respectively, were observed between the three Malaysian isolates and subgroup Bii. Interestingly, phylogenetic analysis indicated the three Malaysian isolates were clustered and formed a new subgroup, tentatively subgroup Bv. Pathogenicity study of one of the isolates, UPM1019/2018 on one-day-old SPF chickens, produced clinical manifestations related to CAstV infection. However, no mortality was recorded throughout the study. Diarrhoea and somnolence were the most observed clinical signs accompanied by decreased feed intake in both the challenged and exposed sentinel groups. Dehydration, cachexia, ballooned intestines were observed on post-mortem examinations. Three birds (two from the challenged group and one from the exposed sentinel group) exhibiting enlarged kidneys and ureters with urate deposits and visceral gout were observed on days 6 and 9 postinoculation. Microscopically, the observable lesions were mild lymphocytic aggregates in the duodenum, tubular degeneration and interstitial nephritis. Real-time RT-PCR assay detected CAstV RNA from the cloacal swabs of both the challenged and exposed sentinel groups throughout the study. The highest mean virus copy number (log10 13.23) was on day 3 post-inoculation in the challenged group. In contrast, the exposed sentinel group has a peak mean virus copy number (log10 9.04) on day 6 postinoculation. In conclusion, the isolated Malaysian CAstV is pathogenic in SPF chickens, causing lesions in the gut and kidneys in both the infected and exposed chickens. Although the studied CAstV are classified under group B, they are distinct from other CAstV strains forming a new subgroup Bv.